Deep Roots Support New Branches: The Impact of Dynamic, Cross-Generational Rural Culture on Older Women’s Response to Formal Health Care - Christine M Eisenhauer; Jennifer L Hunter; Carol H Pullen (Online Journal of Rural Nursing and Health Care, 2012)
Rural, older adults experience marked disparity in access to quality health care when compared to their urban counterparts. One aspect of promoting health access to these individuals that has received little attention is rural cultural competence. Semi-structured interviews and review of cultural artifacts informed this case study of a rural, community-dwelling, 83 year old woman who is co-managing her chronic disease with the formal healthcare system. The purpose of the study was to situate the life story of one rural, elderly woman within the context of the rural culture that she has experienced, and, through the application of Bonder, Martin, and Miracle’s (2002) Culture Emergent Theory, illuminated the theoretical and practical aspects of how dynamic culture influences health care practices and nurse-client encounters. Recommendations discussed include individual and system level strategies for developing cultural awareness, cultural knowledge, cultural skill, methods for participating in cultural encounters, and considerations for growing cultural desire. These strategies are considered imperative for the promotion of culturally competent rural nursing, nursing education, and rural patient advocacy.